2003
DOI: 10.1172/jci200319441
|View full text |Cite
|
Sign up to set email alerts
|

Induction of FoxP3 and acquisition of T regulatory activity by stimulated human CD4+CD25– T cells

Abstract: CD4+CD25+ regulatory T (TR) cells have been described in both humans and mice. In mice, TR are thymically derived, and lack of TR leads to organ-specific autoimmunity. Recently, the forkhead/winged helix transcription factor, FoxP3, has been shown to be important for the function of TR cells in mice. In this study, human TR cells were examined and, in results similar to those of studies done in mice, expression of FoxP3 was found exclusively in CD4+CD25+ T cells and correlated with the suppressive activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Broadly speaking, an equivalent pattern of FOXP3 expression has now also been reported in human cells, with Treg-like properties being similarly transferable by retroviral transduction (48)(49)(50)(51). Already, however, some discrepancies are beginning to emerge between the behavior of human and that of mouse FOXP3/Foxp3 expression.…”
Section: Foxp3 As a Master Control Gene For Treg Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Broadly speaking, an equivalent pattern of FOXP3 expression has now also been reported in human cells, with Treg-like properties being similarly transferable by retroviral transduction (48)(49)(50)(51). Already, however, some discrepancies are beginning to emerge between the behavior of human and that of mouse FOXP3/Foxp3 expression.…”
Section: Foxp3 As a Master Control Gene For Treg Developmentmentioning
confidence: 93%
“…Already, however, some discrepancies are beginning to emerge between the behavior of human and that of mouse FOXP3/Foxp3 expression. For instance, there is at least 1 example of FOXP3 being apparently induced following standard antibodymediated activation of normal CD25 -human T cells; this has not been observed thus far in the murine model (50). Similarly, some instances of CD25 -human T cell activation by DCs have also resulted in FOXP3 upregulation (refs.…”
Section: Foxp3 As a Master Control Gene For Treg Developmentmentioning
confidence: 99%
“…CD25 is not a specific marker of Tregs, as it is also upregulated upon conventional T cell activation. Recently, a transcription factor (FoxP3) has been described to be specifically expressed in humans by thymic and peripheral regulatory CD8 + and CD4 + CD25 + T cells (20,21). To determine whether the increased levels of CD4 + CD25 + and CD8 + CD25 + T cells observed in SIVagm-infected AGM were Tregs or conventional activated T cells, we quantified FoxP3 transcript levels in PBMCs of the same 6 animals.…”
Section: Figurementioning
confidence: 99%
“…Some studies have suggested that Foxp3 expression delineates a distinct lineage of regulatory T cells (28). Other studies have shown that Foxp3 is induced by in vitro activation of CD4 + CD25 -human peripheral lymphocytes, which acquire the surface expression of CD25 in addition (29). More recently, CD4 + regulatory T cells have been induced by low doses of antigenic peptide, which suggests that induction of regulatory T cells may be an outcome of weak TCR stimulation (30).…”
Section: Introductionmentioning
confidence: 99%